قصيدة مزمور المروق للشّاعر ميداني بن عمر ــــ دراسة في توازي زوايا الإدهاش - الأقرع, حسين; بن خليفة, مشري (جامعة الوادي - university of Eloued, 2020)
إنَّ خلو قصيدة النَّثر من الوزن والقافية واعتمادها على مبدأ التَّوازي اللَّفظي والدَّلالي الذي تفرضه بنية الجملة جعلها تختلف في جوهرها عن الشِّعر العمودي والتّفعيلة؛ ومن هذا الباب بدأ الطعن! ولذا كان من الإنصاف أن أقول :إنّ الانتقاد الذي تعرضت له قصيدة النَّثر حوّلها إلى مسخ؛ وقد ظُلمت، من أجل هذا جاءت هذه الدراسة لتقف على أبرز الانتقادات وحجج أصحابها، والرَّدّ عليهم بطريقة تجمع بين العلميّة والأدبيّة في محاولة لشرح مبدأ نظرية التّوازي لبناء قصيدة النّثر في النّقد العربي المعاصر. . الكلمات المفتاحية : قصيدة النّثر ؛ التّوازي ؛ الشّعريّة ؛ الاختيار ؛ الانزياح . Abstract The absence of rhythm and rhyme from prose poem and its dependence on the principle of semantic and pragmatic parallelism imposed by the sentence structure made it different in its essence from the classical Arabic poetry; hence, from this very point criticism started. It seems fair to say that the criticism given to the prose poem turned it into a monster. This study, therefore, seeks to explore the most prominent criticisms and the arguments of some critics, and attempts to respond to them in a scientific and literary manner in a bid to explain the principle of parallelism theory for building prose poem in contemporary Arab criticism. Keywords: prose poem; parallelism; poetry; choice; displacement.
مقال
Keywords: قصيدة النّثر ؛ التّوازي ؛ الشّعريّة ؛ الاختيار ؛ الانزياح; prose poem; parallelism; poetry; choice; displacement.